"Stick to Sports": Evidence from Sports Media on the Origins and Consequences of Newly Politicized Attitudes. (4th July 2022) - Peterson, Erik; Muñoz, Manuela
ABSTRACT: Politics now intrudes into many aspects of social life. How does this occur and what are its consequences? We study the sources of politicized attitudes toward ESPN, a sports media outlet involved in controversies where politics and sports intersect, and consider their implications for sports news use. We assess two potential contributors to politicized attitudes toward ESPN: exposure to political media criticizing the network and encounters with its sports coverage. In survey-linked web browsing data and a survey experiment, exposure to political media led the public to evaluate ESPN in political terms, showing messages from political elites can affect opinions of entertainment media. In contrast, exposure to ESPN's typical sports coverage failed to alter views of the network. We also find these newly politicized attitudes do not reduce use of ESPN, demonstrating the intrusion of politics into a seemingly apolitical setting may not displace other considerations underlying behavior.